A packaging bag material with strong antibacterial property and preparation method thereof
By using polyhydroxyalkanoate and polypithylcarbonate materials, combined with starch and other components, the problems of poor antibacterial performance and difficulty in degradation of existing polyethylene materials are solved, and efficient antibacterial and biological Degradation effect.
Patent Information
- Application Number
- CN202310182449.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-01
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-03-01
AI Technical Summary
Although existing polyethylene materials have good mechanical properties in food packaging bags, they have poor antibacterial properties and are difficult to degrade, resulting in environmental pollution.
Materials such as polyhydroxyalkanoate and polypropylene carbonate are used, and antibacterial masterbatches prepared from starch, polyvinyl alcohol, nanotitanium dioxide and other components are added, and combined with degradation accelerator to prepare a packaging with strong antibacterial properties and easy degradation. Bag material.
It improves the antibacterial properties and degradation speed of packaging bag materials, improves the mechanical properties and freshness effect of the materials, and reduces environmental pollution.
Smart Images

Figure GDA0005198577280000061 
Figure GDA0005198577280000081 
Figure GDA0005198577280000091
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of polymer materials, and more specifically, to a packaging bag material with strong antibacterial properties and a preparation method thereof. Background Art
[0002] Plastic packaging and plastic packaging products occupy an increasingly larger share in the market, especially composite plastic flexible packaging, which has been widely used in food, medicine, chemical and other fields, among which food packaging accounts for the largest proportion, such as beverage packaging, frozen food packaging, steamed food packaging, fast food packaging, etc. These products have brought great convenience to people's lives. Among them, plastic packaging film is one of the most widely used materials in plastic packaging.
[0003] At present, plastics have been widely used in food packaging materials. Polyethylene film is odorless, non-toxic, has good moisture absorption resistance, and has good solvent resistance and chemical stability. This makes polyethylene film a packaging material that is widely used in food transportation, food packaging, daily necessities packaging and other fields.
[0004] In the prior art, a Chinese invention patent application document with application number 2020116067647 discloses a polyethylene material for food packaging bags, wherein the raw materials include by weight: 80-100 parts of polyethylene, 10-20 parts of impact modifier, 8-10 parts of filler, 0.1-0.3 parts of stearic acid, and 2-3 parts of compatibilizer, wherein the filler is talcum powder, organic nano-montmorillonite and modified graphene.
[0005] With respect to the above-mentioned related technologies, the inventors found that although the current polyethylene materials have good mechanical properties, their antibacterial properties are poor, and polyethylene is difficult to degrade, causing great pollution to the environment. Summary of the invention
[0006] In order to improve the antibacterial properties of food packaging bag materials and make the packaging bags easy to degrade, the present application provides a packaging bag material with strong antibacterial properties and a preparation method thereof.
[0007] In the first aspect, the present application provides a packaging bag material with strong antibacterial properties, which adopts the following technical solution:
[0008] A packaging bag material with strong antibacterial properties, comprising the following components in parts by weight: 60-90 parts of polyhydroxyalkanoate, 20-30 parts of polypropylene carbonate, 0.5-1 parts of zinc acetate, 3-6 parts of plasticizer, 5-15 parts of antibacterial masterbatch, 1-4 parts of antioxidant, and 0.8-3.2 parts of degradation accelerator;
[0009] The antibacterial masterbatch comprises: 2-6 parts of starch, 1-3 parts of polyvinyl alcohol, 0.1-0.3 parts of nano titanium dioxide, 0.2-0.5 parts of nano silicon dioxide, 0.25-0.5 parts of soluble rare earth salt, 0.05-0.1 parts of silane coupling agent and 1-3 parts of loofah fiber.
[0010] By adopting the above technical scheme, polyhydroxyalkanoate is used as the main base material of the packaging bag material, and polypropylene carbonate and zinc acetate are used in combination, not only can a blended material with excellent comprehensive performance be prepared, but also the material can be completely biodegradable without losing its complete biodegradability, thereby improving the mechanical effect of polyhydroxyalkanoate and improving the tensile properties of the packaging bag; polyhydroxyalkanoic acid is a degradable plastic with good environmental effects and certain gas barrier properties, so that the packaging bag prepared can extend the shelf life of fruits and vegetables; in addition, a degradation accelerator is added to accelerate the degradation rate of the packaging bag material made of raw materials such as polyhydroxyalkanoate and polypropylene carbonate; antibacterial masterbatch is prepared with components such as starch, polyvinyl alcohol, nano-silicon dioxide, and loofah fiber, wherein nano-titanium dioxide has photocatalytic antibacterial properties, and loofah fiber contains tannin The antibacterial ingredients such as loofah fiber can make the packaging bag material have antibacterial effect, and the loofah fiber is biodegradable and does not affect the degradation rate of the packaging bag material. The soluble rare earth salt can inhibit the growth of strains, thereby improving the antibacterial rate of the packaging bag material. Starch is a natural high molecular weight polysaccharide. The hydroxyl groups in the dehydrated glucose unit on the molecular chain have certain reactivity and can undergo substitution reaction with silane coupling agent. The silane coupling agent is grafted onto the molecular chain to achieve hydrophobic modification of starch. Starch can form a blended material with polypropylene carbonate having hydroxyl groups at the end through hydrogen bonding. The molecular chains between starch and polypropylene carbonate are mutually entangled and penetrated, which improves the interface transfer stress between starch and polypropylene carbonate, thereby improving the dispersibility of PPC and antibacterial masterbatch and improving the mechanical effect of the packaging bag material.
[0011] Optionally, the method for preparing the antibacterial masterbatch comprises the following steps:
[0012] The starch, soluble rare earth salt, silane coupling agent and distilled water are mixed, heated to 45-60°C, stirred for 4-5 hours, cooled to room temperature, filtered, the precipitate is washed with anhydrous ethanol and then vacuum dried to obtain modified starch;
[0013] The luffa fiber is added to deionized water, heated to 70-80° C., stirred for 6-8 hours, and filtered to obtain a luffa extract; polyvinyl alcohol is made into a polyvinyl alcohol aqueous solution with a mass concentration of 4-6%, nano-titanium dioxide and nano-silicon dioxide are added, ultrasonically dispersed for 20-30 minutes, and dried to obtain a pretreated polyvinyl alcohol;
[0014] The loofah extract and the modified starch are mixed to prepare a blended emulsion, which is then mixed with the pretreated polyvinyl alcohol and extruded into granules.
[0015] By adopting the above technical scheme, starch and soluble rare earth salt are firstly pretreated with silane coupling agent, the coupling agent is grafted onto starch molecules, and the soluble rare earth salt can be evenly dispersed with starch under the action of silane coupling agent; the loofah fiber is mixed with deionized water for water extraction to obtain the loofah extract containing inorganic salts, sugars, tannins, proteins, amino acids, alkaloid salts, organic acid salts and other substances that can be dissolved in water, among which tannins and glycosides have antibacterial function; polyvinyl alcohol is then mixed with nano titanium dioxide and nano silicon dioxide, and the nano silicon dioxide is mixed with the nano titanium dioxide to obtain the loofah extract; the nano silicon dioxide is mixed with the nano titanium dioxide to obtain the loofah extract; the nano silicon dioxide is mixed with the nano titanium dioxide to obtain the loofah extract; the nano silicon dioxide is mixed with the nano titanium dioxide to obtain the loofah extract; the nano silicon dioxide is mixed with the nano titanium dioxide to obtain the loofah extract; the nano silicon dioxide is mixed with the nano titanium dioxide to obtain the loofah extract; the nano silicon dioxide is mixed with the nano titanium dioxide to obtain the loofah extract; the nano silicon dioxide is mixed with the nano titanium dioxide to obtain the loofah extract; the nano silicon dioxide is mixed with the nano silicon ... silicon dioxide to obtain the loofah extract; the nano silicon dioxide is mixed with the nano titanium dioxide to obtain the loofah extract; the nano silicon dioxide is mixed with the nano silicon dioxide to obtain the loofah extract; the nano silicon dioxide is mixed with the nano silicon The siloxane bonds react with the hydrophilic groups of polyvinyl alcohol to change the hydrophilic properties of polyvinyl alcohol. The incorporation of nano-titanium dioxide can improve the combination reaction effect of the siloxane bonds and the hydrophilic groups of polyvinyl alcohol, fill the pores in the network structure of polyvinyl alcohol, change the permeation path of water molecules, reduce the water permeability of polyvinyl alcohol, thereby changing the water permeability of the antibacterial masterbatch, and then reduce the moisture permeability of the packaging bag material. Finally, the pretreated polyvinyl alcohol, modified starch and loofah extract are mixed and extruded to obtain the antibacterial masterbatch. The preparation method is simple, and the antibacterial masterbatch not only has antibacterial properties, but also has moisture-barrier and fresh-keeping effects.
[0016] Optionally, the polyhydroxyalkanoate comprises polyhydroxybutyrate and poly(3-hydroxybutyrate-co-3-hydroxyvalerate) in a mass ratio of 0.3-0.6:1.
[0017] By adopting the above technical scheme, the physical and mechanical properties of polyhydroxybutyrate (PHB) are similar to those of polypropylene, and it is biodegradable. Its degradation products in nature are carbon dioxide and water. It also has good biocompatibility. Poly (3-hydroxybutyrate-co-3-hydroxyvalerate) is a degradable polymer material produced by biological fermentation, and has excellent mechanical properties and biocompatibility. By blending polyhydroxybutyrate and poly (3-hydroxybutyrate-co-3-hydroxyvalerate) with polypropylene carbonate, a packaging bag material with good flexibility and complete biodegradability can be made.
[0018] Optionally, the degradation accelerator is prepared by mixing and extruding the following components in parts by weight: 1-3 parts of polylactic acid, 0.05-0.1 parts of organic acid, 0.5-1.5 parts of polyethylene glycol, 0.09-0.27 parts of organic montmorillonite and 0.5-1.5 parts of EVOH.
[0019] By adopting the above technical scheme, the degradation accelerator is prepared using components such as polylactic acid and organic acid. The polylactic acid is completely biodegradable and has good biocompatibility, and can be fully mixed with polyhydroxyalkanoates and the like. In addition, the use of organic acids can undergo autotrophic reactions in a natural environment to produce peroxides, and the peroxides decompose into free radicals under light, causing the polymer chain to break and degrade. In addition, polylactic acid is hydrophilic, and the mixing of polyethylene glycol is beneficial to improving the hydrophilicity of polylactic acid, thereby wetting the surface of the packaging bag, making it easier for microorganisms to attach to the surface of the packaging bag, thereby accelerating the degradation of the packaging bag. In addition, the addition of EVOH and organic montmorillonite can improve the barrier properties of polylactic acid to oxygen and water vapor, so that the packaging bag material has a surface hydrophilic but impermeable effect, thereby improving the preservation ability of the packaging bag for fruits and vegetables.
[0020] Optionally, the soluble rare earth salt comprises cerium humate and samarium chloride in a mass ratio of 1:0.3-0.5.
[0021] By adopting the above technical solution, cerium humate and samarium chloride are rare earth salts with strong antibacterial ability, which can inhibit the growth of strains and improve the bactericidal effect of the antibacterial masterbatch.
[0022] Optionally, the packaging bag material with strong antibacterial properties also includes a preservative in an amount of 4-8 parts.
[0023] By adopting the above technical solution, when the packaging bag material is used to package fruits, vegetables and other materials, adding a preservative can improve the storage time of fruits and vegetables and extend the preservation effect of the packaging bag.
[0024] Optionally, the preservative comprises the following components in parts by weight: 1-2 parts of aloe nanosilver colloid, 5-8 parts of EVA, 1-2 parts of chitosan fiber, and 0.03-0.07 parts of silane coupling agent.
[0025] By adopting the above technical scheme, the aloe nano-silver colloid contains aloe and nano-silver particles, the nano-silver particles have good antibacterial properties, the aloe film has barrier properties, the EVA is biodegradable, has good mechanical properties and strong barrier properties, the chitosan fiber can kill bacteria and inhibit bacterial reproduction, and the silane coupling agent can improve the compatibility of the chitosan fiber, the aloe nano-silver colloid and the EVA.
[0026] Optionally, the chitosan fiber is prepared by pre-treating bamboo nanocellulose whiskers, specifically by the following method:
[0027] The bamboo nanocellulose whiskers were mixed with water and ultrasonicated for 20-30 minutes to obtain a bamboo nanocellulose whisker suspension. The bamboo cellulose suspension was mixed and impregnated with chitosan fibers and vacuum dried.
[0028] By adopting the above technical scheme, nanocellulose whiskers are impregnated on chitosan fibers. The unique morphological structure and surface properties of nanocellulose whiskers enable the nanocellulose whiskers to form a dense network structure, thereby providing excellent oxygen barrier properties, thereby improving the oxygen barrier properties of chitosan fibers and improving the preservation effect of packaging bag materials.
[0029] Preferably, the antioxidant is selected from one or more of antioxidant 1010 and antioxidant 168; the plasticizer is selected from one or more of epoxidized soybean oil, white oil, glycerol, polyethylene glycol, and citric acid.
[0030] In a second aspect, the present application provides a method for preparing a packaging bag material with strong antibacterial properties, using the following technical solution:
[0031] A method for preparing a packaging bag material with strong antibacterial properties comprises the following steps:
[0032] The polyhydroxyalkanoate is mixed with polypropylene carbonate and zinc acetate, and the mixture is extruded and granulated to prepare a pre-treated masterbatch;
[0033] The pretreated masterbatch is mixed with the antibacterial masterbatch, the preservative, the plasticizer, the antioxidant and the degradation accelerator, and the mixture is extruded and granulated to obtain a packaging bag material with strong antibacterial property.
[0034] By adopting the above technical scheme, polyhydroxyalkanoate, polypropylene carbonate and zinc acetate are first blended and granulated, and zinc acetate is used as an ester exchange catalyst to prepare a blended material with excellent mechanical properties, and finally mixed with the remaining materials and granulated. The preparation method is simple and the prepared packaging bag material has good antibacterial properties.
[0035] In summary, this application has the following beneficial effects:
[0036] 1. Since the present application adopts polyhydroxyalkanoate, polypropylene carbonate and the like to prepare the packaging bag material, and incorporates the antibacterial masterbatch prepared by components such as starch, polyvinyl alcohol, and soluble rare earth salts, and since polyhydroxyalkanoate and polypropylene carbonate are biodegradable, the mechanical properties of the two are improved after blending, and the terminal hydroxyl groups of polypropylene carbonate are not capped, thereby connecting with the hydroxyl groups in starch, thereby improving the compatibility of the antibacterial masterbatch and polypropylene carbonate. In addition, loofah fiber, soluble rare earth salt and nano titanium dioxide have antibacterial properties, which can improve the antibacterial ability of the packaging bag.
[0037] 2. In the present application, polylactic acid, organic acid, polyethylene glycol and other components are preferably used to prepare the degradation accelerator. Polylactic acid has good hydrophilicity. The addition of polyethylene glycol can improve the hydrophilicity of polylactic acid, thereby making the surface of the packaging bag material hydrophilic, which is convenient for the attachment of microorganisms on the surface of the packaging bag material. The addition of EVOH and organic montmorillonite improves the barrier property of polylactic acid, thereby making the surface of the packaging bag hydrophilic but not water-permeable, which is convenient for degradation and has good antibacterial and fresh-keeping effects.
[0038] 3. In the present application, aloe nano-silver colloid, chitosan fiber, EVA and silane coupling agent are preferably used to prepare the preservative. Chitosan fiber and aloe nano-silver colloid have antibacterial properties, and aloe nano-silver colloid has certain barrier properties. EVA has barrier and degradable effects. The prepared preservative can improve the moisture retention of the packaging bag material and improve the preservation effect. DETAILED DESCRIPTION
[0039] Preparation Example 1-3 of Antibacterial Masterbatch
[0040] Preparation Example 1: (1) 1 kg of cassava starch, 0.25 kg of soluble rare earth salt, 0.05 kg of silane coupling agent KH550 and 2 kg of distilled water were mixed, heated to 45° C., stirred for 4 h, cooled to room temperature, filtered, and the precipitate was washed with anhydrous ethanol and vacuum dried at 80° C. for 3 h to obtain modified starch, wherein the soluble rare earth salt includes cerium humate and samarium chloride in a mass ratio of 1:0.3;
[0041] (2) adding 1 kg of loofah fiber into 2 kg of deionized water, heating to 70° C., stirring for 8 h, and filtering to obtain a loofah extract;
[0042] (3) 1 kg of polyvinyl alcohol was prepared into a polyvinyl alcohol aqueous solution with a mass concentration of 4%, 0.1 kg of nano-titanium dioxide and 0.2 kg of nano-silicon dioxide were added, ultrasonically dispersed for 20 minutes, and dried to obtain pretreated polyvinyl alcohol;
[0043] (4) Mixing the loofah extract and modified starch to prepare a blended emulsion, mixing it with the pretreated polyvinyl alcohol, and extruding and granulating it at 170° C.
[0044] Preparation Example 2: (1) 2 kg of cassava starch, 0.5 kg of soluble rare earth salt, 0.1 kg of silane coupling agent KH550 and 4 kg of distilled water were mixed, heated to 60° C., stirred for 5 h, cooled to room temperature, filtered, and the precipitate was washed with anhydrous ethanol and vacuum dried at 80° C. for 3 h to obtain modified starch. The soluble rare earth salt included cerium humate and samarium chloride in a mass ratio of 1:0.5; (2) 3 kg of loofah fiber was added to 3 kg of deionized water, heated to 80° C., stirred for 6 h, filtered, and a loofah extract was obtained;
[0045] (3) 3 kg of polyvinyl alcohol was prepared into a polyvinyl alcohol aqueous solution with a mass concentration of 6%, 0.3 kg of nano-titanium dioxide and 0.5 kg of nano-silicon dioxide were added, ultrasonically dispersed for 30 minutes, and dried to obtain pretreated polyvinyl alcohol;
[0046] (4) Mixing the loofah extract and modified starch to prepare a blended emulsion, mixing it with the pretreated polyvinyl alcohol, and extruding and granulating it at 170° C.
[0047] Preparation Example 3: 2kg of cassava starch, 1kg of polyvinyl alcohol, 0.1kg of nano-titanium dioxide, 0.2kg of nano-silicon dioxide, 0.25kg of soluble rare earth salt, 0.05kg of silane coupling agent KH550 and 1kg of loofah fiber are mixed evenly, extruded and granulated at 170°C to obtain an antibacterial masterbatch. The soluble rare earth salt includes cerium humate and samarium chloride in a mass ratio of 1:0.3.
[0048] Example
[0049] Example 1: A packaging bag material with strong antibacterial properties, the raw material dosage of which is shown in Table 1, wherein the plasticizer in Table 1 is epoxidized soybean oil, the antioxidant is antioxidant 1010, the degradation accelerator is made by mixed extrusion of 1 kg polylactic acid, 0.05 kg organic acid, 0.5 kg polyethylene glycol, 0.09 kg organic montmorillonite and 0.5 kg EVOH, the polyhydroxyalkanoate includes polyhydroxybutyrate (PHB) and poly (3-hydroxybutyrate-co-3-hydroxyvalerate) in a mass ratio of 0.3:1, the PHB brand is 9200, and the antibacterial masterbatch is made by Preparation Example 1.
[0050] The method for preparing the packaging bag material with strong antibacterial properties comprises the following steps:
[0051] The polyhydroxyalkanoate is mixed with polypropylene carbonate and zinc acetate, and the mixture is extruded and granulated to prepare a pre-treated masterbatch;
[0052] The pretreated masterbatch is mixed with the antibacterial masterbatch, a plasticizer, an antioxidant and a degradation accelerator, and extruded and granulated at 170° C. to obtain a packaging bag material with strong antibacterial properties.
[0053] Table 1 Amount of raw materials used for packaging bag materials in Examples 1-4
[0054]
[0055] Example 2: A packaging bag material with strong antibacterial properties. The difference from Example 1 is that the raw material dosage is as shown in Table 1, the antibacterial masterbatch is made from Preparation Example 2, the degradation accelerator is made by mixed extrusion of 3kg polylactic acid, 0.1kg organic acid, 1.5kg polyethylene glycol, 0.27kg organic montmorillonite and 1.5kg EVOH, and the polyhydroxyalkanoate includes polyhydroxybutyrate (PHB) and poly (3-hydroxybutyrate-co-3-hydroxyvalerate) in a mass ratio of 0.6:1.
[0056] Example 3-4: A packaging bag material with strong antibacterial properties, which is different from Example 1 in that the amounts of raw materials used are as shown in Table 1.
[0057] Example 5: A packaging bag material with strong antibacterial properties. The difference from Example 1 is that the antibacterial masterbatch is made from Preparation Example 3.
[0058] Example 6: A packaging bag material with strong antibacterial properties, which is different from Example 1 in that polyethylene glycol is not added to the degradation accelerator.
[0059] Example 7: A packaging bag material with strong antibacterial properties, which is different from Example 1 in that EVOH and organic montmorillonite are not added to the degradation accelerator.
[0060] Embodiment 8: A packaging bag material with strong antibacterial properties, which differs from Embodiment 1 in that it further contains 4 kg of preservative, which is prepared by the following method: 1 kg of chitosan fiber, 1 kg of aloe nano-silver colloid, 0.03 kg of silane coupling agent KH550 and 3 kg of water are mixed, the temperature is raised to 60°C, the mixture is stirred for 2 hours, the mixture is dried and blended with 5 kg of EVA, and the mixture is extruded and granulated; the preparation method of the aloe nano-silver colloid is as follows: 1 kg of aloe juice is squeezed, deionized water of twice its mass is added, the juice is heated to boiling and then filtered, a silver ammonia solution is added to the filtrate, the mixture is reacted at room temperature for 2 hours, and the aloe nano-silver colloid with a concentration of 3.6 mg / L is prepared;
[0061] The chitosan fiber is pretreated with bamboo nanocellulose whiskers, specifically, the fresh bamboo is crushed into bamboo pulp, mixed with a sulfuric acid solution with a concentration of 60wt% in a mass ratio of 1:9, stirred at 55°C for 30min, centrifuged, the supernatant is removed, washed with water until neutral, and dried to obtain bamboo nanocellulose whiskers, the bamboo nanocellulose whiskers are mixed with water, ultrasonicated for 20min to obtain a bamboo nanocellulose whisker suspension, the bamboo cellulose suspension is mixed with the chitosan fiber, impregnated, and vacuum dried;
[0062] The method for preparing a packaging bag material with strong antibacterial properties comprises the following steps:
[0063] The polyhydroxyalkanoate is mixed with polypropylene carbonate and zinc acetate, and the mixture is extruded and granulated to prepare a pre-treated masterbatch;
[0064] The pretreated masterbatch is mixed with the antibacterial masterbatch, the preservative, the plasticizer, the antioxidant and the degradation accelerator, and the mixture is extruded and granulated to obtain a packaging bag material with strong antibacterial property.
[0065] Embodiment 9: A packaging bag material with strong antibacterial properties, which differs from Embodiment 1 in that it further contains 8 kg of preservative, which is prepared by the following method: 2 kg of chitosan fiber, 2 kg of aloe nano-silver colloid, 0.07 kg of silane coupling agent KH550 and 3 kg of water are mixed, heated to 60°C, stirred for 2 hours, dried, blended with 8 kg of EVA, and extruded into granules; the preparation method of aloe nano-silver colloid is: 1 kg of aloe juice is squeezed, deionized water of twice its mass is added, heated to boiling and filtered, silver ammonia solution is added to the filtrate, reacted at room temperature for 2 hours, and aloe nano-silver colloid with a concentration of 3.6 mg / L is prepared;
[0066] The chitosan fiber is pretreated with bamboo nanocellulose whiskers, and the specific method is as follows: fresh bamboo is crushed into bamboo pulp, mixed with a sulfuric acid solution with a concentration of 60wt% in a mass ratio of 1:9, stirred at 55°C for 30min, centrifuged, the supernatant is removed, washed with water until neutral, and dried to obtain bamboo nanocellulose whiskers, the bamboo nanocellulose whiskers are mixed with water, ultrasonicated for 20min to obtain a bamboo nanocellulose whisker suspension, the bamboo cellulose suspension is mixed with chitosan fibers, impregnated, and vacuum dried.
[0067] Example 10: A packaging bag material with strong antibacterial properties, which is different from Example 9 in that the chitosan fibers are not pretreated with bamboo nanocellulose whiskers.
[0068] Example 11: A packaging bag material with strong antibacterial properties, which is different from Example 9 in that no aloe nanosilver colloid is added to the preservative.
[0069] Example 12: A packaging bag material with strong antibacterial properties, which differs from Example 9 in that chitosan fiber is not added.
[0070] Example 13: A packaging bag material with strong antibacterial properties, which differs from Example 9 in that EVA is not added.
[0071] Example 14: A packaging bag material with strong antibacterial properties, which is different from Example 9 in that the preservative is sodium alginate.
[0072] Comparative Example
[0073] Comparative Example 1: A packaging bag material with strong antibacterial properties, which is different from Example 1 in that nano titanium dioxide and nano silicon dioxide are not added to the antibacterial masterbatch.
[0074] Comparative Example 2: A packaging bag material with strong antibacterial properties, which is different from Example 1 in that no loofah fiber is added to the antibacterial masterbatch.
[0075] Comparative Example 3: A packaging bag material with strong antibacterial properties, which is different from Example 1 in that no soluble rare earth salt is added to the antibacterial masterbatch.
[0076] Comparative Example 4: A packaging bag material with strong antibacterial properties, which differs from Example 1 in that no degradation accelerator is added.
[0077] Comparative Example 5: A polyethylene material for food packaging bags, wherein the raw materials include, by weight: 80 g polyethylene, 20 g methyl methacrylate-butadiene-styrene copolymer, 4 g talcum powder, 2 g organic nano-montmorillonite, 2 g modified graphene, 0.3 g stearic acid, 1 g polyethylene grafted maleic anhydride copolymer, and 1 g silane coupling agent;
[0078] In the preparation process of modified graphene, 0.4268g (0.002mol) of dodecyldimethyl tertiary amine was dissolved in 100ml of ethanol, and then 0.4769g (0.0024mol) of 3-chloropropyltrimethoxysilane was added and mixed, the temperature was raised to 60°C in a water bath, stirred for 48h, and the ethanol was removed by reduced pressure evaporation to obtain an intermediate material; 5g of graphene oxide was evenly dispersed in 300ml of ethanol by ultrasonication, and then 20ml of ethanol aqueous solution containing 0.25g of the intermediate material was added and mixed, and the grafting reaction was carried out at 85°C with stirring for 4h, filtered, the filter cake was washed, and dried to obtain the modified graphene.
[0079] Performance testing
[0080] The packaging bag material was prepared according to the methods in the examples and comparative examples, and various properties were tested according to the following methods. The test results are recorded in Table 2.
[0081] 1. Antibacterial property: tested according to GB / T 31402-2015 "Test method for antibacterial performance of plastic surface", the test results are Escherichia coli (ATCC25922) and Staphylococcus aureus (ACTT6538);
[0082] 2. Weight loss degradation rate: The new material prepared in the embodiment or comparative example is buried in a constant humidity sealed container filled with soil with a pH value of 6-7, taken out on the 83rd day, washed with deionized water, dried, and placed at room temperature for 24 hours for equilibrium, and then weighed to calculate the degradation rate, degradation rate (%) = (mass before degradation - mass after degradation) / mass before degradation × 100%;
[0083] 3. Tensile strength: The new material prepared in the embodiment or comparative example is added into a film blowing machine for film blowing treatment, and a film is blown out at 120°C, and then the film is cooled to room temperature to form a packaging bag with a thickness of 1.1 mm, and tested in accordance with GB / T1040-2006 "Determination of tensile properties of plastics";
[0084] 4. Fresh-keeping effect: The new material prepared in the embodiment or comparative example is added into a film blowing machine for film blowing treatment, and a film is blown out at 120° C. The film is then cooled to room temperature to form a packaging bag with a thickness of 1.1 mm. The water vapor permeability is tested according to GB / T1037-1988 "Test method for water vapor permeability of plastic film and sheet - cup method", and the oxygen permeability is tested according to GB / T31354-2014 "Test method for oxygen permeability of packages and containers".
[0085] Table 2 Performance test of packaging bag materials with strong antibacterial properties
[0086]
[0087]
[0088] Combining the data in Examples 1-4 and Table 2, it can be seen that the packaging bag materials prepared in Examples 1-4 have a high antibacterial effect on Escherichia coli and Staphylococcus aureus, and the degradation rate reaches more than 80% after 83 days, with high tensile strength and good mechanical properties.
[0089] In Example 5, the antibacterial masterbatch prepared in Preparation Example 3 is used. The antibacterial masterbatch is prepared by simply mixing various raw materials. Compared with Example 1, the antibacterial property of the packaging bag material prepared in Example 5 is reduced.
[0090] Compared with Example 1, in Example 6, no polyethylene glycol was added to the degradation accelerator. After the packaging bag material prepared in Example 6 was placed in the soil for 83 days, the degradation rate decreased, indicating that polyethylene glycol can improve the biodegradation rate of the packaging bag material.
[0091] Compared with Example 1, no organic montmorillonite is added to the degradation promoter in Example 7. It can be seen from the data in Table 2 that the barrier effect of the packaging bag material prepared in Example 7 on oxygen and water vapor is weakened, the permeability of oxygen and water vapor is increased, and the tensile strength is reduced. This shows that the addition of EVOH and organic montmorillonite can effectively improve the barrier properties of the packaging bag material, improve its preservation effect, and also improve its mechanical strength.
[0092] Compared with Example 1, Example 8 and Example 9 further added a preservative to the packaging bag material. The data in Table 2 show that the antibacterial effect of the packaging bag materials prepared in Example 8 and Example 9 is improved, and still has a high degradation rate, the water vapor and oxygen permeability are significantly reduced, the barrier properties are improved, and the preservation effect is improved.
[0093] In Example 10, compared with Example 9, the chitosan fibers are not pretreated with bamboo nanocellulose whiskers. The packaging bag material prepared in Example 10 has a weakened barrier effect against oxygen and water vapor, and a reduced freshness-preserving effect.
[0094] Compared with Example 9, Example 11 and Example 12 do not add aloe nanosilver colloid in Example 11, and do not add chitosan fiber in Example 12. The antibacterial rate of the packaging bag materials made in Example 11 and Example 12 is reduced, the antibacterial effect is weakened, the permeability of oxygen and water vapor is increased, and the preservation effect is reduced.
[0095] Compared with Example 9, in Example 13, no EVA is added as the preservative, and the other properties of the packaging bag material made in Example 13 do not change much, but the barrier performance to water vapor and oxygen is reduced.
[0096] In Example 14, sodium alginate is used as a preservative, the barrier property of the packaging bag material is significantly reduced, and the preservation effect is weakened.
[0097] Compared with Example 1, Comparative Example 1 does not add nano titanium dioxide and nano silicon dioxide. Table 2 shows that the antibacterial and fresh-keeping properties of the material prepared in Comparative Example 1 are reduced.
[0098] Compared with Example 1, Comparative Example 2 did not add loofah fiber. The antibacterial property of the packaging bag material made in Comparative Example 2 was reduced, the degradation rate did not change much, and the barrier effect was not significantly improved, indicating that loofah fiber can improve the antibacterial property of the packaging bag material without affecting its degradation rate.
[0099] Compared with Example 1, Comparative Example 3 does not add soluble rare earth salt. It can be seen from the data in Table 2 that the addition of soluble rare earth salt improves the antibacterial property of the packaging bag material.
[0100] Compared with Example 1, Comparative Example 4 does not add a degradation accelerator. The degradation rate of the packaging bag material prepared in Comparative Example 4 is significantly reduced, and the barrier property to water vapor and oxygen is weakened.
[0101] Comparative Example 5 is a packaging material prepared by the prior art, which has a low antibacterial rate, poor antibacterial effect, and is difficult to degrade.
[0102] The new materials prepared in Example 1 and Examples 8-14 were used to make packaging bags, and the preservation effect was tested at 35°C and 65% environment. The test objects were cherries. The cherries packaged in Example 1 rotted on the 3rd day, the cherries packaged in Examples 8 and 9 rotted on the 8th day, the cherries packaged in Examples 12 and 13 rotted on the 5th day, and the cherries packaged in Examples 11 and 10 rotted on the 7th day. Therefore, it can be seen that in Examples 8 and 9, the new materials prepared by adding the preservatives can make the packaging bags have better density and better preservation effect, which is helpful to extend the shelf life of fruits and vegetables and achieve long-term preservation of fruits and vegetables.
[0103] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A packaging bag material with strong antibacterial properties, characterized in that: The invention comprises the following components in parts by weight: 60-90 parts of polyhydroxyalkanoate, 20-30 parts of polypropylene carbonate, 0.5-1 parts of zinc acetate, 3-6 parts of plasticizer, 5-15 parts of antibacterial masterbatch, 1-4 parts of antioxidant, and 0.8-3.2 parts of degradation accelerator; The antibacterial masterbatch comprises: 2-6 parts of starch, 1-3 parts of polyvinyl alcohol, 0.1-0.3 parts of nano titanium dioxide, 0.2-0.5 parts of nano silicon dioxide, 0.25-0.5 parts of soluble rare earth salt, 0.05-0.1 parts of silane coupling agent, and 1-3 parts of loofah fiber; The preparation method of the antibacterial masterbatch comprises the following steps: The starch, soluble rare earth salt, silane coupling agent and distilled water are mixed, heated to 45-60°C, stirred for 4-5 hours, cooled to room temperature, filtered, the precipitate is washed with anhydrous ethanol and then vacuum dried to obtain modified starch; Adding loofah fibers into deionized water, heating to 70-80° C., stirring for 6-8 hours, and filtering to obtain a loofah extract; The polyvinyl alcohol is made into a polyvinyl alcohol aqueous solution with a mass concentration of 4-6%, nano-titanium dioxide and nano-silicon dioxide are added, ultrasonically dispersed for 20-30 minutes, and dried to obtain pretreated polyvinyl alcohol; The loofah extract and the modified starch are mixed to prepare a blended emulsion, which is mixed with the pretreated polyvinyl alcohol and extruded into granules; The degradation accelerator is prepared by mixing and extruding the following components in parts by weight: 1-3 parts of polylactic acid, 0.05-0.1 parts of organic acid, 0.5-1.5 parts of polyethylene glycol, 0.09-0.27 parts of organic montmorillonite and 0.5-1.5 parts of EVOH.
2. The packaging bag material with strong antibacterial properties according to claim 1, characterized in that: The polyhydroxyalkanoate includes polyhydroxybutyrate and poly(3-hydroxybutyrate-co-3-hydroxyvalerate) in a mass ratio of 0.3-0.6:
1.
3. The packaging bag material with strong antibacterial properties according to claim 1, characterized in that: The soluble rare earth salt comprises cerium humate and samarium chloride in a mass ratio of 1:0.3-0.
5.
4. The packaging bag material with strong antibacterial properties according to claim 1, characterized in that: The packaging bag material with strong antibacterial property also includes a preservative, the dosage of which is 4-8 parts.
5. The packaging bag material with strong antibacterial properties according to claim 4, characterized in that: The preservative comprises the following components in parts by weight: 1-2 parts of aloe nanosilver colloid, 5-8 parts of EVA, 1-2 parts of chitosan fiber, and 0.03-0.07 parts of silane coupling agent.
6. The packaging bag material with strong antibacterial properties according to claim 5, characterized in that: The chitosan fiber is prepared by pre-treating bamboo nanocellulose whiskers, and the specific method is as follows: The bamboo nanocellulose whiskers were mixed with water and ultrasonicated for 20-30 minutes to obtain a bamboo nanocellulose whisker suspension. The bamboo cellulose suspension was mixed and impregnated with chitosan fibers and vacuum dried.
7. The packaging bag material with strong antibacterial properties according to claim 1, characterized in that: The antioxidant is selected from one or more of antioxidant 1010 and antioxidant 168; the plasticizer is selected from one or more of epoxidized soybean oil, white oil, glycerol, polyethylene glycol, and citric acid.
8. The method for preparing a packaging bag material with strong antibacterial properties according to any one of claims 1 to 7, characterized in that: The following steps are involved: The polyhydroxyalkanoate is mixed with polypropylene carbonate and zinc acetate, and the mixture is extruded and granulated to prepare a pre-treated masterbatch; The pretreated masterbatch is mixed with the antibacterial masterbatch, the preservative, the plasticizer, the antioxidant and the degradation accelerator, and the mixture is extruded and granulated to obtain a packaging bag material with strong antibacterial property.
Citation Information
Patent Citations
High-strength biodegradable plastic and preparation method thereof
CN114316542A
Macromolecular new material antibacterial plastic bubble bag and preparation method thereof
CN115449199A
Cited By
Biodegradable packaging material and preparation method thereof
CN121271188A